The Influence Of Artificial Intelligence Technology On The Creativity Of Employees At The Tourism Office, Culture, Youth And Sports Dairi Regency - Roy France MTH Sihotang; Mesra B (Yayasan Multidimensi Kreatif, 2024)
The aim of this research is to determine and analyze the influence of Artificial Intelligence on Employee Creativity at the Dairi Regency Tourism, Culture, Youth and Sports Department. This research was carried out at the Dairi Regency Tourism, Culture, Youth and Sports Office. The type of research is associative quantitative. The sample in this study was 96 employees with ASN and honorary status at the Dairi Regency Tourism, Culture, Youth and Sports Office. The sampling technique in this study used the entire population of 96 people. The research results show that Artificial Intelligence has a significant influence on Employee Creativity as shown by the T-Statistic value of 11.310 > 1.660 and the P Value of 0.000 < 0.05. This shows that improvements in Artificial Intelligence can increase employee creativity at the Dairi Regency Tourism, Culture, Youth and Sports Department.